Cognitive Behavioral Group Therapy to reduce depression in survivors of domestic violence - Kurniawan, Yudi; Pratiwi, M.M. Shinta; Pribadi, Agung Santoso; Listya Putri, Cinta Metatarsal; Febriani, Prita; Amalia, Iis; Kusumasari, Fitri (Universitas Mercu Buana Yogyakarta, 2025)
Domestic violence is a national issue that shows an increasing trend in cases from year to year. This study aims to empirically test the effectiveness of Cognitive Behavioural Group Therapy in reducing depression in female survivors of domestic violence. This study used a quasi-experimental design with a pre-test-post-test control group design model. The number of respondents in this study was 16 participants, divided into eight respondents in the experimental group and eight respondents in the control group. The experimental group (n = 8) received Cognitive Behavioural Group Therapy intervention, while the control group (n = 8) was on the intervention waiting list. The level of depression was measured by the Patient Health Questionnaire-9 (PHQ-9) before the intervention, after the intervention, and two weeks after the post-intervention follow-up. The results of the analysis with the independent sample t-test showed a significant difference in the mean depression score between the control and experimental groups in the post-test phase (after being given Cognitive Behavioural Group Therapy), with a p-value of 0.000 (p <0.05). In conclusion, this research proves that Cognitive Behavioural Group Therapy is effective in reducing depression in female survivors of domestic violence. Cognitive Behavioural Group Therapy interventions have an impact on depression levels even after the intervention sessions have ended (as evidenced by the measurement of depression scores in the follow-up sessions). Keyword : Cognitive Behavioral Group Therapy; depression; domestic violence survivors.